Investigation of blood biomarkers for the diagnosis of mild to moderate asthma in horses. (16th May 2019) - Gy, Clementine; Leclere, Mathilde; Vargas, Amandine; Grimes, Carolyn; Lavoie, Jean‐Pierre
Abstract: Background: Asthma in horses is associated with nonspecific respiratory clinical signs and may be manifested only as exercise intolerance. Its diagnosis relies on bronchoalveolar lavage fluid (BALF) cytology in the presence of compatible clinical signs. The identification of blood biomarkers for this condition would facilitate diagnosis in the field, because there are regional areas where BAL is not routinely performed in clinical practice. Objective: Identification of blood biomarkers for the diagnosis of asthma in horses. Animals: Fourteen horses with asthma with increased neutrophil numbers in BALF (neutrophilic asthma), 9 healthy control horses, and 10 horses with other pathologic conditions (pathologic controls). Methods: Physical examination, clinical score, hematology, and BALF cytology (in a subset of horses) were performed. Serum concentrations of surfactant protein D (SP‐D), haptoglobin, and secretoglobin (SCGB) were measured using commercial ELISA assays. Results: Serum concentration of SP‐D > 43 ng/mL, serum concentration of haptoglobin >5730 ng/mL, and serum concentration of SCGB <19 ng/mL allowed differentiation of horses with neutrophilic asthma from horses of the control groups (healthy and pathologic) with sensitivity of 55, 95, and 75%, and specificity of 67, 28, and 60%, respectively. Specificity of 100% and sensitivity of 45% were obtained with the combination of SP‐D, haptoglobin, and SCGB at the serum concentrations indicated above. Specificity of 95% and sensitivity of 45% were obtained with the combination of SP‐D and SCGB serum concentrations. Conclusions and Clinical Importance: Haptoglobin, SCGB, and SP‐D may be diagnostic aids in horses with clinical signs of lower airway disease and neutrophilic pulmonary inflammation.